SOX1 antibodies in sera from patients with paraneoplastic neurological syndromes - Stich, Oliver; Jarius, Sven (Acta neurologica Scandinavica, 2012)
Objectives??? SOX1 antibodies have been described in patients with Lambert?Eaton myasthenic syndrome (LEMS) in association with voltage?gated calcium channel antibodies as serological markers of small cell lung cancer (SCLC). This study was aimed to screen for additional SOX1 autoimmunity in onconeural antibody?positive sera from patients with paraneoplastic neurological syndromes (PNS) other than LEMS and to identify the clinical?immunological profile and associated tumours of patients with coexisting SOX1 antibodies. Methods? We retrospectively analysed sera from 55 patients with different PNS positive for well?characterized antineuronal antibodies for the presence of SOX1 antibodies by recombinant ELISA and immunoblot. Results? Eight (14.5%) patients showed additional SOX1 antibodies in the ELISA and the recombinant immunoblot. Five patients had coexisting Hu antibodies, while the other three showed coexisting CV2/CRMP5, amphiphysin, and coexisting CV2/CRMP5 and Hu antibodies, respectively. PNS included (partially overlapping) subacute sensory neuropathy, subacute sensorimotor neuropathy, cerebellar degeneration, brainstem encephalitis, encephalomyelitis and limbic encephalitis. No tumour was detected in two patients, while the others had lung cancer (four SCLC and two non?SCLC). One patient showed SOX1?specific intrathecal antibody synthesis. Conclusions? We describe SOX1 reactivity for the first time overlapping with CV2/CRMP5 and amphiphysin antibodies. SOX1 reactivity is predominantly associated with Hu antibodies and SCLC, but can occur also in other types of lung cancer. Neurological manifestations present in patients with coexisting SOX1 antibodies and well?characterized antineuronal antibodies do not differ from those previously described in patients positive for antineuronal antibodies but no SOX1?specific anti?glial antibodies.